Tracking cave shape development with microseismic data - Lynch, R; Meyer, S; Lotter, E; Lett, J (Caving 2018: Proceedings of the Fourth International Symposium on Block and Sublevel Caving, 2018)
Microseismic monitoring is routinely used by block and panel caving mines worldwide to track cave shape development. The standard practice is to use the cloud of seismic event locations as a proxy for cave growth below. Careful seismic sensor array planning overcomes problems with event location reliability due to seismicray bending around the unknown cave. However, the aseismic gap – the (unknown) zone between actual cave back and bottom of the seismic event cloud – complicates estimation of cave geometry. More information than simple seismic event locations can be used to infer the cave shape and position. Since seismic events slip according to the stresses acting locally at the source locations, an analysis of source mechanisms yields indications of principal stresses around the cave. These stresses are the result of the virgin stresses perturbed by the cave shape, and this yields information about the cave shape. The apparent seismic wave arrivals under the straightray assumption are retarded when rays bend around the cave. These anomalous travel times are used to create 'spaghetti' – 3D curved lines indicating the likely ray path followed. Analysis of these curved rays in space and time suggests where the cave is and where it is growing. All of this indirect information is now routinely used at Cadia East mine in Australia to estimate the cave shape, helping geotechnical engineers to better manage the cave. A direct verification of the estimated cave shape with an open hole drilled to the cave back in early 2017 provided some validation of these seismic data techniques.
Keywords: cave tracking